PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) DI NAGARI BALIMBING, KECAMATAN RAMBATAN, KABUPATEN TANAH DATAR, SUMATERA BARAT - Febriani Febriani; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2022)
Poverty is still a problem in the world, including Indonesia. One form of handling it is by empowering the community through the KUBE program. One of them is in the Jorong Bukit Tamasu area, Nagari Balimbing which is named KUBE Palano Jaya. The purpose of this research to analyze the implementation of empowerment for the KUBE Palano Jaya beneficiary group and analyze the impact after the empowerment had been given to the Palano Jaya KUBE beneficiary group. Aspects of this research is the implementation includes the preparation stage, the implementation stage, the business development stage, the termination stage and the impact includes positive impacts, outputs, and outcomes. The method used in this study is a qualitative research method. The results of this research indicate that KUBE Palano Jaya is still in the developing stage because the business carried out is still in a small scope. In addition, in the sustainability of the Palano Jaya KUBE business development, there are no future plans. Therefore, he is only running his current business, namely saving and borrowing members and renting rice fans. The impact after the assistance to KUBE Palano Jaya has not been able to fully meet the needs of group members.